Chapter La memoria come impegno civile. Il racconto della Resistenza nell'Italia repubblicana - CALVETTO, Silvano (Public History of Education. Teorie, esperienze, strumenti, 2022)
In modern societies two processes seem to be carried on simultaneously. On one side, the traditional shape assumed by historical knowledge seems dissolving. On the other side, another exigence has to be affirmed: the necessity to remember, to share their memories. This is a pattern linked to the limits and contradictions which characterised the relationship between present and past. Tracing the steps thanks to which the anti-fascist Resiatance have been taking place in Italy is useful for defining the strong ethic and politic relevance making it a precious tool for democratic convivence.